THE EFFECTIVENESS OF SUBSIDIZED FERTILIZER DISTRIBUTION ON RICE PRODUCTIVITY IN TIDAL SWAMP LANDS - Nasir Nasir; Septia Utami Asryansyah; Ursula Damayanti; Gusti Fitriyana; Sri Rahayu Endang Lestari; Ekanopi Aktiva (PT. Jurnal Center Indonesia Publisher, 2026)
The agriculture sector plays a strategic role in the national economy and is highly dependent on fertilizer availability on support crop productivity. This study aimed to analyze the effectivenss of subsidized fertilizer distribution and its impact on rice productivity in the tidal lowland areas of Tanjung Lago District, Banyuasin Regency. The research employed both quantitative and qualitative descriptive approaches using a stratified random sampling method involving 60 farmers who received subsidized fertilizer and 30 farmers who did not reveive subsidizer fertilizer. The effectiveness of subsidizer fertilizer distribution was evaluated using a likert scale based on the Six Appropriateness Principles, while the impct on rice productivity was analyzed by comparing the productivity levels of the two farmer groups. The findings showed that the distribution of subsidized fertilizer was generally categorized as moderately effective, with an average effectiveness score of 71,33%. The price compliance indicator was classified as highly effective (91,66%), while location suitability was categorized as effective (81,00%). Meanwhile, quantity appropriateness, fertilizer type suitability, and timeliness of distribution were categorized as moderately effective. The findings showed that the distribution of subsidized fertilizer was generally categorized as moderately effective, with an average effectiveness score of 71.33%. The price compliance indicator was classified as highly effective (91.66%), while location suitability was categorized as effective (81.00%). Meanwhile, quantity appropriateness, fertilizer type suitability, and timeliness of distribution were categorized as moderately effective. In contrast, the fertilizer quality suitability indicator was still considered ineffective, with an effectiveness score of 55%. The use or subsidized fertilizer also contributed positively to rice productivity. Farmers receiving subsidized fertilizer achieved an average rice productivity of 3.77 ton ha⁻¹, whereas farmers who did non receive subsidized fertilizer produced an average productivity of 3.20 ton ha⁻¹. This resulted in a productivity defference of 0.57 ha⁻¹.. equivalent to approximately 17.81%.